WORKSHOP IMPLEMENTASI KURIKULUM MERDEKA DAN PENYUSUNAN MODUL AJAR PADA GURU PAUD DI KECAMATAN KAMPAR - Nelti Rizka; Zahrati Mansoer; Syarif Sumantri (Yayasan Wayan Marwan Pulungan, 2023)
The independent curriculum is one of the efforts to restore learning after the Covid-19 pandemic. The teacher's ability to implement the curriculum will be a benchmark in the successful implementation of the ongoing curriculum. The purpose of this community service is to provide a solution to the problem of teachers' lack of understanding regarding the implementation of the independent curriculum and the preparation of teaching modules in the Early Childhood Education unit (PAUD). Participants in this activity were 44 PAUD teachers in Kampar District. Activities carried out through four stages, namely First; made direct observations regarding the Implementation of the Independent Curriculum in one of the schools that have implemented the independent sharing curriculum, namely Mutiara Bunda Kindergarten Bangkinang Kota, Second; to reflect and discuss the results of observations, Third; presentation of the independent curriculum concept, Fourth; assisting in the preparation of teaching modules, and Fifth; Practice and Simulation of the Implementation of the Independent Curriculum with workshop participants. The results obtained from this activity were in the form of increasing teachers' understanding of the implementation of the independent curriculum after the workshop was held. Increased understanding of participants related to the concept of an independent curriculum, preparation of KOSP, preparation of teaching modules, Project for Strengthening Pancasila Student Profiles, Learning Assessments, and Implementation Practices of Independent Curriculum Workshop participants responded that this activity was very useful so that they would soon apply the independent curriculum in their respective schools accordance with the concept and practice that has been done.